2007
DOI: 10.2193/2005-534
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Scaup Nest Success and Duckling Survival on the Yukon Flats, Alaska

Abstract: Over the last 20 years scaup numbers have declined, and these declines have been greatest in the northern boreal forests of Canada and Alaska where most lesser scaup (Aythya affinis) nest. We studied nest success and duckling survival of lesser scaup over 3 field seasons, 2001–2003, on the Yukon Flats National Wildlife Refuge in northeastern Alaska, USA. Daily survival rate (DSR) of nests on our study area across all 3 years was 0.943 (n = 177 nests, 95% CI: 0.930–0.954), corresponding to a nest success of onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
(38 reference statements)
1
20
0
1
Order By: Relevance
“…However, at the Erickson breeding site, Koons and Rotella (2003) reported estimates of nest success (11%) and duckling survival (20%) during 1999-2000 to be low and similar to rates recorded for recent studies in boreal forest areas (Fournier and Hines 2001;Brook 2002;Corcoran et al 2007;Martin 2007). In southern Saskatchewan, in 1999-2000, Brook (2002 reported lower nest success (3%) and duckling survival (38% Dawson and Clark 1996) than at Yellowknife (14% and 61%, respectively).…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…However, at the Erickson breeding site, Koons and Rotella (2003) reported estimates of nest success (11%) and duckling survival (20%) during 1999-2000 to be low and similar to rates recorded for recent studies in boreal forest areas (Fournier and Hines 2001;Brook 2002;Corcoran et al 2007;Martin 2007). In southern Saskatchewan, in 1999-2000, Brook (2002 reported lower nest success (3%) and duckling survival (38% Dawson and Clark 1996) than at Yellowknife (14% and 61%, respectively).…”
Section: Introductionsupporting
confidence: 75%
“…For boreal breeding scaup, historical nutrient reserve data are sparse (body mass only; Trauger 1971) but lipid reserves of boreal females measured during [2003][2004] in northern Alberta and the Northwest Territories were much lower than historical values reported for females in northwestern Minnesota in 1986-1988and southwestern Manitoba in 1977-1980(Anteau and Afton 2004, 2009a; but see DeVink et al 2008c). Furthermore, recent studies have reported that some reproductive parameters, such as nest success, female survival, duckling and brood survival, and breeding probability, were low in boreal and parkland breeding sites, at rates that would be consistent with the SCH (Fournier and Hines 2001;Brook 2002;Koons and Rotella 2003;Corcoran et al 2007;Martin et al 2009). Afton and Anderson (2001) and Anteau and Afton (2009a) speculated that reduced food resources at nonbreeding areas would affect body condition and, hence, recruitment of northern boreal breeders more than southern prairie-parkland breeders because of the shorter time between arrival and egg-laying in the north.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations